1996
DOI: 10.1074/jbc.271.38.23185
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Free Radical-catalyzed Generation of Thromboxane-like Compounds (Isothromboxanes) in Vivo

Abstract: The isoprostanes (IsoPs) are novel bioactive prostaglandin-like compounds produced in vivo by free radical-catalyzed peroxidation of arachidonyl-containing lipids. Previously, we have identified IsoPs containing F-type and D- and E-type prostane rings that are formed by reduction and rearrangement of IsoP endoperoxide intermediates, respectively. We now explore whether thromboxane B2 (TxB2)-like compounds, termed B2-isothromboxanes (B2-IsoTxs), are formed by rearrangement of IsoP endoperoxides. Detection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 21 publications
0
59
0
5
Order By: Relevance
“…This extended area of the TLC plate was determined to contain F 3 -IsoPs by analyzing small 5-mm cuts using approaches for their identification described below. The M-⅐CH 2 C 6 F 5 ions were monitored for quantification (m/z 567 for F 3 total amount of F 3 -IsoPs was determined by integrating the peak area of material in the m/z 567 channel in comparison with the m/z 573 channel. GC/NICI/MS was carried out using an Agilent Technologies 6890N Network GC/MS system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extended area of the TLC plate was determined to contain F 3 -IsoPs by analyzing small 5-mm cuts using approaches for their identification described below. The M-⅐CH 2 C 6 F 5 ions were monitored for quantification (m/z 567 for F 3 total amount of F 3 -IsoPs was determined by integrating the peak area of material in the m/z 567 channel in comparison with the m/z 573 channel. GC/NICI/MS was carried out using an Agilent Technologies 6890N Network GC/MS system.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of these compounds proceeds through the generation of bicyclic endoperoxide PGH 2 -like intermediates that are reduced to PGF 2 -like compounds termed F 2 -IsoPs (1) or undergo rearrangement to PGD 2 and PGE 2 -like compounds (D 2 /E 2 -IsoPs) (2) and thromboxane-like compounds (isothromboxanes) (3). Unlike cyclooxygenase-derived PGs, IsoPs are formed in situ esterified to phospholipids and are subsequently released, presumably by the action of a phospholipase A 2 (4).…”
mentioning
confidence: 99%
“…The isoprostanes were originally discovered in 1990 by Morrow et al, [64] and are now believed to act as potent mediators of oxidative injury [64][65][66][67][68]. As such, the isoprostanes are mainly generated from arachidonic acid non-enzymatically and are synthesised in situ in phospholipids and then released through the actions of phospholipases, such as phospholipase A 2 [64,65].…”
Section: Isoprostanes and Tp Receptor Activationmentioning
confidence: 99%
“…A wide range of prostanoid-like isoprostanes is generated including the PGF 2α -, the PGD 2 -, and PGE 2 -series [64,69]. The F 2 series are the most common and one of these compounds 8-epi PGF 2α , also recently termed iPF 2α -III [69], is the most abundant isoprostane generated in situations of oxidative injury [64][65][66][67][68][69]. More recently, similar free-radical derived isomers of other polyunsaturated fatty acids have been described [69,70].…”
Section: Isoprostanes and Tp Receptor Activationmentioning
confidence: 99%
“…Their formation proceeds via PGH 2 -like bicyclic endoperoxide intermediates, which are reduced to form F-ring IsoPs (F 2 -IsoPs) (1) or undergo rearrangement to form D-ring and E-ring IsoPs (2) and isothromboxanes (3). Recently, we reported that IsoP endoperoxide intermediates also undergo rearrangement to form highly reactive ␥-ketoaldehyde levuglandin-like compounds (4).…”
mentioning
confidence: 99%